Role of lipid transfers in the formation of a subpopulation of small high density lipoproteins. - G J Hopkins; L B Chang; P J Barter (Journal of Lipid Research, 1985)
The effect of lipid transfers on the structure and composition of high density lipoproteins (HDL) has been studied in vitro in incubations that contained the lipoprotein-free fraction of human plasma as a source of lipid transfer protein. These incubations did not contain lecithin:cholesterol acyltransferase activity and were not supplemented with lipoprotein lipase. Incubations were performed at 37 degrees C for 6 hr in both the presence and absence of either added very low density lipoproteins (VLDL) or the artificial triglyceride emulsion, Intralipid. Incubation in the absence of added VLDL or Intralipid had little or no effect on the HDL. By contrast, incubation in the presence of either VLDL or Intralipid resulted in marked changes in the HDL. The effect of incubation with VLDL was qualitatively similar to that of Intralipid; both resulted in obvious transfers of lipid and changes in the density, particle size, and composition of HDL. Incubation of the plasma fraction of density 1.006-1.21 g/ml, total HDL, or HDL3 with either VLDL or Intralipid resulted in the following: 1) a depletion of the cholesteryl ester and free cholesterol content and an increase in the triglyceride content of both HDL2 and HDL3; 2) a decrease in density and an increase in particle size of the HDL3 to form a population of HDL2-like particles; and 3) the formation of a discrete population of very small lipoproteins with a density greater than that of the parent HDL3. The newly formed lipoproteins had a mean particle radius of 3.7-3.8 nm and consisted mainly of protein, predominantly apolipoprotein A-I and phospholipid.